2021
DOI: 10.1101/2021.06.28.21259338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution of Anti-SARS-CoV-2 IgG Antibody and IgG Avidity Post Pfizer and Moderna mRNA Vaccinations

Abstract: Messenger RNA (mRNA) based vaccines (Pfizer/BioNTech and Moderna) are highly effective at providing immunity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, there is uncertainty about the duration of immunity, evolution of IgG antibody levels and IgG avidity (an index of antibody-antigen binding strength), and differences in the immune responses between vaccines. Here we performed a prospective pilot study of 71 previously COVID-19 free subjects upon receiving both doses of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Using DBS, we saw that vaccinated individuals’ spike IgG antibody levels increased until several weeks after their last dose before beginning to slowly decline, matching results from other studies that used serum/plasma ( 17 19 ). Vaccinated individuals’ spike IgG also reached higher levels than were seen in those who were infected but not yet vaccinated ( 18 , 20 26 ).…”
Section: Discussionsupporting
confidence: 79%
“…Using DBS, we saw that vaccinated individuals’ spike IgG antibody levels increased until several weeks after their last dose before beginning to slowly decline, matching results from other studies that used serum/plasma ( 17 19 ). Vaccinated individuals’ spike IgG also reached higher levels than were seen in those who were infected but not yet vaccinated ( 18 , 20 26 ).…”
Section: Discussionsupporting
confidence: 79%
“…Vaccination seems to play a major role in proper avidity maturation by prolonging the availability of antigens. As the post-vaccination antibody concentration wanes over time, higher avidity may sustain immunity and maintain the ability to fight viral infection at reduced antibody levels [ 16 ]. Overall, repeated vaccinations increase antibody avidity towards the mutated S protein of the Omicron variant, supporting the idea that antibodies with high avidity and high neutralizing potential can increase cross-protection against variants that carry several mutations on the RBD.…”
Section: Discussionmentioning
confidence: 99%
“…Immune responses towards the SARS-CoV-2 nucleoprotein, S protein, and RBD following natural infection are characterized by incomplete avidity maturation, as also observed in other coronavirus infections [ 14 , 15 ]. By contrast, studies conducted on recipients of one or two doses of vaccines have reported an increase in antibody avidity, suggesting potential antibody maturation after vaccination [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We would also like to remark that in our study we did not disclaim the existence of a correlation between anti-RBD IgG levels and neutralizing bioactivity in vaccinated individuals nor that the high neutralizing activity we assessed at 6 months is necessarily protective, since the 1 month-apart swab-based monitoring protocol we use might have missed asymptomatic carriers. Actually, we observed an increasing strength of correlations from T2 and T3 despite a declining titer of anti-RBD IgG, likely as a result of affinity maturation of IgG by somatic hypermutation of spike/RBD-specific B cells [13] , [14] , [15] . This temporal trend has already been tracked after SARS-CoV-2 vaccination [12] and implies that an absolute conversion factor between anti-RBD IgG levels and neutralizing titers would be unreliable.…”
mentioning
confidence: 99%
“…As opposite, the studies cited by Lippi and Plebani [16] , [17] were not designed to provide data on anti-RBD IgG and neutralizing activity and their correlation on the long-term, when divergent kinetics may become apparent. Should a neutralizing antibodies absolute threshold of protection ever become available (hopefully using the WHO International Standard), implementation of the anti-RBD IgG level as a time-independent standalone correlate of protection may confuse risk stratification [14] .…”
mentioning
confidence: 99%